2D-shear wave elastography in the prediction of type II endoleaks after endovascular aneurysm repair. Issue 1 (1st February 2021) - Bando, Yuya; Kitase, Masanori; Shimohira, Masashi; Honda, Junichi; Furuta, Yoshiteru; Kasuya, Akihiro; Imada, Hidenao; Mizutani, Masaru; Shibamoto, Yuta
Abstract: Purpose: To evaluate the usefulness of 2D-shear wave elastography (2D-SWE) in the prediction of type II endoleaks after endovascular aneurysm repair (EVAR) of abdominal aortic aneurysms (AAA). Material and methods: Twenty-nine patients underwent EVAR for AAA, and 2D-SWE was performed after EVAR. Follow-up contrast-enhanced CT and ultrasonography were performed to evaluate endoleaks in all patients. The median follow-up period was 12 months (range, 3–12 months). Patients were divided into two groups: one with an endoleak (endoleak group) and another without it (control group). We compared the elasticity index (EI) of intraluminal thrombus (ITL) and fresh thrombus (FT) between the two groups. Results: Type II endoleaks were confirmed in five of the 29 patients (endoleak group), and there were no endoleaks in the other 24 (control group). ILT was observed in 21 patients of the control group and in all patients of the endoleak group. There was a difference only in EI of ILT; the mean EI (± standard deviation) of ILT was 89 ± 16 kPA in the control group and 113 ± 25 kPA in the endoleak group ( p =.037). Conclusions: High EI of ILT may predict the occurrence of type II endoleaks after EVAR of AAA.